2010
DOI: 10.1111/j.1708-8240.2010.00322.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Various Resin Composite Shades and Layering Technique with a Shade Guide

Abstract: Overall, the L*, a*, and b* values of the enamel composite shades were significantly different from the corresponding VST. Only a few layered composites matched the L*, a*, and b* of the keyed VST. Out of the 72 combinations, 20 (28%) resulted in DeltaE*(ab) below the 3.3 clinically perceptible limit. CLINICAL SIGNIFICANCE Composite shades do not match well to the Vita shade guide tabs, even when the layering technique is used. As demonstrated in this study, only a few composites matched the corresponding Vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 17 publications
5
46
0
1
Order By: Relevance
“…translucency, opacity, and surface gloss) may be affected by several factors including quality and quantity of light reflection at the surface, dispersion, diffraction and interference of light at the surface, roughness and anatomical morphology of surface, properties and structures of enamel and dentin (2,(17)(18)(19), and variations of blood flow in the dental pulp (20,21). Light also affects the gum and lip color (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…translucency, opacity, and surface gloss) may be affected by several factors including quality and quantity of light reflection at the surface, dispersion, diffraction and interference of light at the surface, roughness and anatomical morphology of surface, properties and structures of enamel and dentin (2,(17)(18)(19), and variations of blood flow in the dental pulp (20,21). Light also affects the gum and lip color (22).…”
Section: Discussionmentioning
confidence: 99%
“…Orthodontists or patients may encounter unwanted changes on the enamel surface or structure, such as discoloration, white spots, microcracks, fractures, and abrasions during and after fixed orthodontic treatment (FOT) because of, e.g., diet, oral care, bonding materials and techniques, composites, appliances, debonding, and clean-up procedures (1)(2)(3). Bonding materials and composites of FOT are the most prominent factors responsible for enamel color alterations (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, a VITA Classical Shade tab was used as a control with the metal tab holder removed. 16 However, the removal of the lingual part of the tab holder could affect the thickness of the shade tab, and thereby affect the color of the shade tab. In this study, a resin denture tooth was selected for the control because the lingual part of the denture tooth is similar in shape to that of a human tooth without any modifications that could affect the color measurement procedure.…”
Section: Discussionmentioning
confidence: 99%
“…8 Costa et al 16 compared the final shade of resin composites prepared using the layering technique (enamel layer over dentin layer) with the corresponding VITA Classical Shade tabs and reported that only 28% (n = 72) of layered resin composites resulted in ΔE < 3.3, below the clinically perceptible limit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation